2016
DOI: 10.1503/cjs.011415
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the modified Hardinge approach in acetabular positioning

Abstract: Background:The surgical approach chosen for total hip arthroplasty (THA) may affect the positioning of the acetabular component. The purpose of this study was to examine the accuracy in orienting the acetabular component using the modified Hardinge approach. Methods:We used our institutional arthroplasty database to identify patients with primary, press-fit, hemispherical acetabular components of a metal-on-polyethylene THA performed between 2003 and 2011. Patients with radiographs obtained 1-3 years after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Masonis reported that the lowest rate of dislocation after THA occurred with the direct lateral approach (0.55%) compared with the transtrochanteric approach (1.27%), P‐L approach (3.23%), and anterolateral approach (2.18%) 27 . Moreover, Goyal found only one case of dislocation in 1010 patients (0.09%) who underwent THA using the modified Hardinge approach 28 . In our study, we used the modified Hardinge approach and obtained satisfactory results regarding dislocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Masonis reported that the lowest rate of dislocation after THA occurred with the direct lateral approach (0.55%) compared with the transtrochanteric approach (1.27%), P‐L approach (3.23%), and anterolateral approach (2.18%) 27 . Moreover, Goyal found only one case of dislocation in 1010 patients (0.09%) who underwent THA using the modified Hardinge approach 28 . In our study, we used the modified Hardinge approach and obtained satisfactory results regarding dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Classic Safe Zone and Combined Anteversion May Not Be Suitable for THA Using the Lateral Approach Interestingly, many studies have noted that THAs using the lateral approach may lead to a lower rate of implants being positioned properly in the Lewinnek safe zone than THAs using the P-L approach, but THAs using the lateral approach lead to fewer dislocations 5,28 . We also found that only 52.9% of patients had measurements within the Lewinnek safe zone.…”
Section: Different Approaches Exhibit Distinct Implant Orientationsmentioning
confidence: 99%
“…This method involved removing the gluteus medius tendon from its attachment off the trochanter and conducting a subperiosteal dissection from the trochanter continuous with the vastus lateralis tendon [ 29 , 38 ]. The most well-known LA was described by Hardinge and involved splitting the gluteus medius and minimus tendons longitudinally and continuing distally into the vastus lateralis tendon [ 39 ]. Soon after, the anterolateral approach gained popularity and was well developed by Sir Watson-Jones.…”
Section: Approaches In Total Hip Arthroplastymentioning
confidence: 99%
“…THA, one of the greatest advances in orthopedic surgery, can signi cantly improve the quality of life of patients with end-stage hip joint disease, increase function, restore range of joint movement, and relieve pain [9,10]. There are multiple surgical approaches for THA, including traditional posterior approach (PA), anterior approach (AA), lateral approach (LA) and modi ed Hardinge approach [11,12]. These traditional surgical approaches have some common shortcomings of external trochanter muscle injury, postoperative dislocation and longer recovery time [13][14][15].…”
Section: Introductionmentioning
confidence: 99%